Do the Unemployed Accept Jobs Too Quickly? A Comparison with Employed Job Seekers - Simonetta Longhi (Institute for the Study of Labor (IZA), 2015)
This paper analyses differences between unemployed and employed job seekers in job finding rates and in the quality of the job found. Compared to the unemployed, employed job seekers have a smaller pool of job offers that they consider acceptable; this leads to lower job finding rates but better quality jobs. Differences in job quality are tiny when unobserved heterogeneity and selection into accepting a job are accounted for. Hence, differences are mostly due to behaviour of unemployed people rather than negative signaling or employer discrimination.
Keywords: J01; J20; J29; J62; J64; 330; on-the-job search; unemployment; job-finding rate; job quality